The courage of composers and the tyranny of taste : reflections on new music - Varga, Bálint András (Eastman studies in music, 2017)
All-new interviews with 33 of the world's leading composers--from Adams and Crumb to Gubaïdulina and Rihm--give unique insights into the creative process.